Broad band infrared spectroscopy of grooved silicon - PEROVA, TANIA (SPIE, 2005)
Grooved silicon (gr-Si) structures with a period of few micrometers, which were formed by anisotropic etching of (110) Si wafers, have been investigated by means of broad band infrared (IR) and submillimeter transmission spectroscopy. In the spectral region of 50-1000 ?m the results are well explained by an effective medium model, which predicts a strong birefringence with a difference between refractive indices for ordinary and extraordinary beams to be about 0.73-0.77. The IR transmission of gr-Si in the range from 1 to 30 ?m is strongly influenced by light scattering. The experimental results measured in the region 1-5 ?m can be understood in the terms of the geometric optics.
Proceedings of SPIE
Opto-Ireland 2005: Optoelectronics, Photonic Devices, and Optical Networks
PUBLISHED
Dublin, Ireland
Keywords: IR spectroscopy; anisotropic silicon structure; effective medium model